Importance of nasal endoscopy for the evaluation of epistaxis - Ray, Ritam; Mukherjee, Manoj; Dutta, Manotosh; Neogi, Mousumi; Gayen, Ganesh Chandra (Bangladesh Journal of Otorhinolaryngology, 2012)
Objective: To evaluate the effectiveness of nasal endoscopy in cases of epistaxis. Study design: Prospective study Setting: Department of ENT, Burdwan Medical College & Hospital, Burdwan, India. Method: 118 patients with epistaxis presented in the Department of ENT, Burdwan Medical College & Hospital, Burdwan were evaluated with the help of nasal endoscope to find out the hidden cause of epistaxis. Conclusion: Significant pathology was detected in 88 cases (69%) out of 118 cases of epistaxis. Moreover, endoscope guided biopsy was taken in suspected cases and managed according to histopathology report. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10408 Bangladesh J Otorhinolaryngol 2012; 18(1): 11-15